Religion and Culture in Early Modern Europe, 1500-1800. - Von Greyerz, Kasper (Oxford University Press, USA, 2007)
Introduction. I. UPHEAVAL AND RENEWAL. 1. The ripple effects of the Reformation. 1.1. Reformation. 1.2. Counterreformation. 1.3. Confessionalization and the assault on popular culture. 1.4. The so-called Second Reformation. 2. Renewal vs. ossification. 2.1. "Nadere reformatie" and Pietism. 2.2. The Puritans. 2.3. Jansenism. 2.4. Moravians and Methodists. II. THE INTEGRATED, OUTCASTS, AND THE ELECT. 1. Community. 1.1. Reformation, Counterreformation, and community. 1.2. Marriage and family. 1.3. Popular religiosity as a collective ritual. 2. Pariahs. 2.1. The marginalized: Jews. 2.2.